Examining the Effectiveness of Using Bankruptcy as an Ultimum Remedy in Resolving Debt and Receivable Disputes: Case Analysis of PT Jawa Barat Indah - Millatus Shohihah; Ali Murtadho, Nazhif (Dinasti Research, 2024)
Bankruptcy is a condition that causes a person or legal entity to become incompetent in carrying out legal actions. The Bankruptcy Law was originally created to protect creditors by providing a clear and definite mechanism for resolving unpaid debts. Debtors who have difficulty paying their maturing debts and believe that they are unable to continue payments can submit a PKPU to the Commercial Court. In bankruptcy, there are several important principles, one of which is the existence of debt. Debt is the main requirement for filing for bankruptcy, because without debt a bankruptcy case cannot be filed. Bankruptcy should belast resort, namely as the last solution or the last solution of the last in solving the problem. But in reality in the bankruptcy case of PT Jawa Barat Indah, Bankruptcy was just like premium remedy or the first resort. The author will provide a review and portrait of three important things. First, regulation of debt principles in the Bankruptcy Law; Second, bankruptcy principle as last resort; and Third, analysis of the effectiveness of the use of bankruptcy in cases of disputes over debts against the case of PT Jawa Barat Indah. The method in this article is normative juridical, Law No. 37 of 2004 became the primary legal material, library research is the technique of collecting legal materials in this article. Secondary legal material uses theory last resort as a benchmark and tertiary legal material as an elaboration of certain terms. Research results: 1) The principle of debt in UUK-PKPU has two equally strong opinions, namely the narrow angle (principal debt and interest) and the broad angle (performance obligation in civil law). 2) Bankruptcy as the last action after reorganization efforts, to prevent gaps, while filing for bankruptcy requires prior understanding regarding the implementation of agreements and the involvement of Debtors and Creditors.